MEDIA DAN TAFSIR MASKULINITAS: SUATU TINJAUAN ATAS CULTURAL IMPERIALISM - yuhdi fahrimal; asmaul husna (SOURCE : Jurnal Ilmu Komunikasi, 2021)
Masculinity is a topic that has attracted the attention of many researchers. They examine causes, patterns of change, and impacts. This article attempts to understand masculinity in the perspective of cultural imperialism. Through the perspective of cultural imperialism, we find evidence that masculinity is not born from the womb of the local community's culture, but rather as a result of the practice of colonialism and imperialism. In the era of media globalization, cultural imperialism places more emphasis on the psychological aspect where advertisements and television shows set a new standard of masculinity for men. This paper will discuss the influence of cultural imperialism and media hegemony on the construction of masculinity in society.